Impact of selected organizational characteristics on psychological and behavioural outcomes of hotel frontline employees - Nik Mohd Masdek, Nik Rozana; Abdul Aziz, Yuhanis; Awang, Khairil Wahidin (Universiti Putra Malaysia Press, 2011)
This paper explores a model of the effects of empowerment, training, and reward on frontline employees' service recovery performance, job satisfaction, and turnover intentions. Data were collected using questionnaires. The hotel industry was chosen as the platform being surveyed due to the boundary spanning roles of its employees who were underpinned by frequent contacts with customers during their day to day activities. As such, it is most likely that employees, particularly the front-liners, would be individuals who address service failures. Hypotheses were formulated from previous conceptual and empirical studies. In this study, eleven hypotheses were posed to test the inter-linkages between six identified variables. Spearman Correlation was used as the method of analysis, whereby empowerment and training were found to be correlated with service recovery performance, job satisfaction, and turnover intentions. Meanwhile, reward was found to be correlated with only service recovery performance and job satisfaction. Conclusion, limitations and future research direction were also discussed.